Las tecnologías de la información y comunicación en el proceso de enseñanza aprendizaje en el área de matemáticas de los estudiantes de sexto y séptimo grado de educación general básica de la unidad educativa San Pedro de “Vilcabamba” de la parroquia San Pedro de la provincia de Loja, durante el año 2022 - Carlos Eduardo, Ojeda Macanchi (2022)
The present research and curricular integration project has as its theme "Information and communication technologies in the teaching-learning process in the area of mathematics of the sixth and seventh grade students of basic general education of the San Pedro de "Vilcabamba" of the San Pedro parish of the province of Loja, during the year 2022 Being the general objective "Determine the use of ICTs as a didactic tool for the improvement of the teaching-learning process in the area of mathematics in the sixth and seventh grade students of EGB of the San Pedro de "Vilcabamba" educational unit of the San Pedro parish of the Province of Loja, during the year 2022”. being the study subjects 18 students and 1 teacher. In order to obtain true data and on which our research with a quantitative approach is based, an interview was conducted with the teacher in which the teaching method used for learning mathematics can be evidenced. The results obtained from the research prompted the search for a digital tool for education, the Bmath application being selected. Thinking about possible scenarios that require the management of this app, a user manual for said application was created that will serve to reinforce autonomous learning